Properties of pulp fiber filled high density Polyethylene - Azmel Hakim, Zainol Abidin (Universiti Malaysia Perlis, 2008)
In this study, attempt has been made to combine the advantages of fiber and polymer. Composites based on high density polyethylene (HDPE) and pulp fiber was made through melt blending and compression molding. HDPE/pulp fiber composites were prepared by using the Z-blade mixer at processing temperature 190ºC and speed of 35 rpm with different filler loading varying between 0% and 15% by weight. A coupling agent, maleated anhydrate polyethylene (MAPE) was added as filler treatment to improve the adhesion of matrix and filler material. HDPE/pulp fiber composites have been characterized from the point of view of mechanical properties. Addition of pulp fiber into HDPE matrix was enhanced some of tensile and flexural properties. HDPE/ pulp fiber composites were prepared to provide a comparison with the HDPE/treated pulp fiber composites. Although both composites show increasing properties but it was found that HDPE/treated pulp fiber composites exhibit lower tensile strength and flexural strength than those of HDPE/untreated pulp fiber composites. Scanning Electron Microscope (SEM) was used for morphology studies of the tensile fracture surface and particle distribution. From the image capture it exhibit the failure mode transformed from ductile to brittle with increasing filler loading. Finally, water absorption testing was done and the result shows that MAPE was effectively functioned to resist water absorption in the composites.